An analysis of survival in patients with castrate-resistant prostate cancer receiving enzalutamide with treatment breaks. (May 2022) - Rowe, Michael P; Walter, Stuart; Hidayat, Ayesha; Pollard, Adam; Norris, Timothy; Victor, Deborah; McGrane, John; Thomson, Alastair
Objective: Enzalutamide is effective in treating metastatic castrate-resistant prostate cancer (mCRPC) but can have side effects that require treatment breaks (TB). We conducted a retrospective analysis of outcomes of patients who had extended TB due to toxicity compared to continuous dosing. Methods: Patients prescribed enzalutamide for mCRPC from September 2011 to February 2018 were included. TB was defined as an interruption of four weeks or more. Overall survival (OS) from enzalutamide start, time to prostate-specific antigen failure (TTF) and total enzalutamide treatment time (TTT) were analysed for TB and continuous responders (>50% PSA drop), and a significance level of 0.05 was assigned. Results: A total of 110 patients were continuous responders, and 29 had TB. The median number of interruptions was one (range 1–7), and time on treatment was 70% in the TB group. The TB group had significantly improved OS (100 vs. 60 months; hazard ratio=1.8, 95% confidence interval 1.17–2.77, p =0.02), prolonged TTF (median 11 vs. 6 months; p =0.008) and TTT (median 15 vs. 8 months; p =0.0001). Conclusion: Extended TB do not seem to impact OS or treatment duration adversely in patients who are responding and experiencing toxicity, and may be a useful option in managing toxicity. Prospective trials could explore this further. Level of evidence: Level 2c.